Lia e o Sistema de Proteção Social - Magalhães, Bruna Souza (2023)
The ruptures of family ties between parents and children are crossed by vulnerabilities. Significantly, many of those people who have their children under State guardians are women, almost always single mothers, responsible for more than one child. In this sense, the present study has the general objective of understanding which measures need to be taken to care for women who have their children collected by the State, in order to prevent the disruption of family ties. The methodological path is based on the analysis of the Life History of a woman, black, socially vulnerable, mother of five children who are under the guardianship of the State, as well as in the documentary analysis. To achieve this, it was necessary to delve into the area of ​​law and public policies in an attempt to better contemplate the complex theme. The results found point to need for greater effectiveness of basic protection and improvements in training psychology professionals so that, based on the analysis of ethical-political suffering, they can capable of promoting social transformation.